EDUCATION ON GADGET USE FOR SCHOOL-AGE CHILDREN IN THE KALIRUNGKUT VILLAGE, RUNGKUT DISTRICT, SURABAYA CITY - IMA KURNIASTUTI; hendik eko saputro; Chika Tunas Handayani; Dwi Nur Khafidatun Nisa (Community Service Journal of Indonesia, 2026)
The use of gadgets among school children in Indonesia continues to increase in line with the development of digital technology. Although gadgets can provide benefits as a medium for learning and communication, excessive use without supervision can have negative effects, such as decreased concentration on learning, health problems, and the risk of addiction. Based on these conditions, an educational activity on the healthy and wise use of gadgets was held in Kalirungkut Village, Rungkut District, Surabaya City. The method used was interactive counseling combined with question and answer sessions. There were 30 participants aged 5-10 years old. Evaluation was carried out through pre-test and post-test questionnaires. The method used was interactive counseling combined with a question and answer session. There were 30 participants aged 5-10 years old. Evaluation was carried outhrough pre-test and post-test questionnaires to measure the increase in knowledge. The results of the activity showed an increase in understanding of knowledge by 60%, with the initial percentage of 25% (pre-test) to 85%(post-test). This activity proves that interactive education is effective in increasing children's awareness of healthy and responsible gadget use. Parental guidance remains necessary to ensure that these positive habits can be consistently applied in daily life.